2015
DOI: 10.1186/s12888-015-0415-z
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine maintenance program with contracted work/education and low tolerance for non-prescribed drug use: a cohort study of outcome for women and men after seven years

Abstract: BackgroundA seven-year follow-up of heroin dependent patients treated in a buprenorphine-maintenance program combining contracted work/education and low tolerance for non-prescribed drug use. Gender-specific differences in outcome were analysed.MethodsA consecutively admitted cohort of 135 men and 35 women, with eight years of heroin abuse/dependence on average was admitted to enhanced buprenorphine maintenance treatment. Standardized interviews, diagnostic assessments of psychiatric disorders and psychosocial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…As others have suggested, female patients may both gain more benefit from and more easily accommodate to the structure of a substance use clinic. (Öhlin, Fridell, & Nyhlén, 2015) This finding about female advantage for OBOT >1 year retention is consistent with work on short-term treatment retention. (Burns et al, 2015; Öhlin et al, 2015) While women may have better retention than men in OBOT, much remains much to be done to overcome the particular stigma and barriers for women to engage in care in the first place.…”
Section: 0 Discussionsupporting
confidence: 80%
“…As others have suggested, female patients may both gain more benefit from and more easily accommodate to the structure of a substance use clinic. (Öhlin, Fridell, & Nyhlén, 2015) This finding about female advantage for OBOT >1 year retention is consistent with work on short-term treatment retention. (Burns et al, 2015; Öhlin et al, 2015) While women may have better retention than men in OBOT, much remains much to be done to overcome the particular stigma and barriers for women to engage in care in the first place.…”
Section: 0 Discussionsupporting
confidence: 80%
“…These findings suggest that women may do better in BHC‐based MOUD programs over time whereas men are more likely to leave treatment. This may speak to different factors related to women remaining in treatment as seen in prior studies including fewer convictions within the legal system and motivating factors of regaining custody or maintaining relationships with their children …”
Section: Discussionmentioning
confidence: 94%
“…Despite these data, our knowledge of the neural circuitry involved in opioid withdrawal remains incomplete. However, recent studies have shown that sex likely influences these pathways, and may actually affect treatment outcomes (Jimenez-Trevino et al, 2011;Ohlin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A 25-year follow-up of heroin-dependent patients prescribed METH indicated that surviving women were significantly more likely than men to have stopped heroin use (Jimenez-Trevino et al, 2011). Similarly, a 7-year followup study of heroin-dependent patients treated with BUP showed that, again, women were significantly more likely than men to have stopped heroin use (Ohlin et al, 2015). Finally, Sheynin et al (2016) observed that only males receiving replacement therapy (METH or BUP) demonstrated abnormal avoidance behavior.…”
Section: Introductionmentioning
confidence: 99%